Culprit plaque characteristics in women vs men with a first ST‐segment elevation myocardial infarction: In vivo optical coherence tomography insights. Issue 12 (16th December 2017) - Sun, Rong; Sun, Liping; Fu, Yandong; Liu, Huimin; Xu, Maoen; Ren, Xuefeng; Yu, Huai; Dong, Hui; Liu, Yang; Zhu, Yinchun; Tian, Jinwei; Yu, Bo
Abstract : Background: It is unclear whether more severe coronary atherosclerosis is a prerequisite to an initial acute coronary event in women vs men. Hypothesis: Women may have more severe coronary atherosclerosis than men in patients with acute coronary event. Methods: We used intravascular optical coherence tomography (OCT) to evaluate gender differences in culprit‐plaque morphology in patients with a first ST‐segment elevation myocardial infarction (STEMI).We retrospectively enrolled 211 consecutive patients who experienced a first STEMI and underwent an OCT examination of their infarct‐related artery before primary percutaneous coronary intervention. Results: Of the 211 patients enrolled, 162 (76.7%) were men and 49 (23.2%) were women. The women were significantly older than the men (mean age, 60.2 ± 8.2 vs 55.7 ± 11.2 years; P = 0.01) and less likely to be current smokers ( P = 0.02). Moreover, the delay from symptom onset to reperfusion was longer in women than in men (7.6 ± 6.1 vs 5.5 ± 4.4 hours; P = 0.01). The OCT data indicated that there were no gender differences in culprit‐plaque morphology, including lipid length, lipid arc, minimum fibrous cap thickness, or minimum lumen area. Additionally, no gender differences were found in the prevalence of plaque rupture, thin‐cap fibroatheroma, residual thrombus, microvessels, macrophages, cholesterol crystals, or calcification. Conclusions: Among patients presenting with a first STEMI, there were no differences in culprit plaque features between women and men.